PERAN PENYULUH PERTANIAN TERHADAP PENDAPATAN USAHATANI UBI BANGGAI DI DESA ALUL KECAMATAN BULAGI - Pilang, Milawati S.; Pakanyamong, Ambo Abd. Kadir; Enteding, Trianto; Rustiawati, Yuni (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Banggai yam is an endemic plant typical of Sulawesi, especially the people of Banggai Islands. This study aims to determine the role of agricultural extension workers on the income of Banggai Yams farmers in Alul Village, Bulagi Sub-district. This research was conducted in Alul Village, Bulagi Sub-district, Banggai Islands Regency. The selection of the research site was carried out deliberately with the consideration that Banggai Islands Regency is one of the Banggai yam producing districts. This research will be conducted from January to March 2023. This study used methods with likert and income analysis. The income obtained by farmers in Alul Village, Bulagi Sub-district, which is obtained from the deduction between Total revenue (TR) of Rp. 4,650,000 and Total cost (TC) of Rp. 646,077, then income (π) = TR – TC is Rp. 4,003,923. This means that Banggai yam plant farming can still continue to be cultivated or developed by farmers in Alul Village, Bulagi Sub-district, Banggai Islands Regency because the amount of income obtained is still quite high.